2016
DOI: 10.1007/s13311-015-0418-y
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Erythropoietin Short Peptide on Acute Traumatic Brain Injury

Abstract: There is currently no effective medical treatment for traumatic brain injury (TBI). Beyond the immediate physical damage caused by the initial impact, additional damage evolves due to the inflammatory response that follows brain injury. Here we show that therapy with JM4, a low molecular weight 19-amino acid nonhematopoietic erythropoietin (EPO) peptidyl fragment, containing amino acids 28-46 derived from the first loop of EPO, markedly reduces acute brain injury. Mice underwent controlled cortical injury and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…Although the effect of EPO treatment on tissues outside the bone marrow has been found to be not entirely dependent on hematopoiesis (Leist et al, 2004;Wang et al, 2016), we do not know if the effects of EPO treatment observed in the current study are caused by an increase in hematocrit, because hematocrit was not measured. EPO treatment of mice every other day for 3 weeks at the same dosage as used in the current study, 5,000 IU/kg, has been shown to cause an increase in hematocrit that was still detectable 1 week after the secession of treatment, but had abated at 3 weeks (Adamcio et al, 2008).…”
Section: Limitationscontrasting
confidence: 55%
“…Although the effect of EPO treatment on tissues outside the bone marrow has been found to be not entirely dependent on hematopoiesis (Leist et al, 2004;Wang et al, 2016), we do not know if the effects of EPO treatment observed in the current study are caused by an increase in hematocrit, because hematocrit was not measured. EPO treatment of mice every other day for 3 weeks at the same dosage as used in the current study, 5,000 IU/kg, has been shown to cause an increase in hematocrit that was still detectable 1 week after the secession of treatment, but had abated at 3 weeks (Adamcio et al, 2008).…”
Section: Limitationscontrasting
confidence: 55%
“…Wang et al showed that EPO improved neurological functions in the experimental ischemia model. In another study, Brines et al showed that the infarct area was smaller in the rat brain with EPO treatment and it had a cell-protecting effect [9]. It was also shown that when EPO is applied in the central nervous system after a stroke, it decreased apoptosis and brain edema [12].…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral nervous system is more successful in axonal regeneration as inhibitor myelin proteins are less dominant and Schwann cells are more active in distal. Therefore, agents considered to increase nerve regeneration are frequently used in experimental studies where peripheral nerve damage is formed [9,10]. Although medications, such as methylprednisolone and gabapentin, are proven to be effective on post-traumatic nerve injuries (spinal cord traumas and peripheral nerve injuries, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations